CFD Investigation of A New Elliptical-Bladed Multistage Savonius Rotors - Khalid Mrigua; Abdelghani Toumi; Mounia Zemamou; Bader Ouhmmou; Yahya Lahlou; Mohammed Aggour (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
The Savonius-conventional wind turbine is a class of wind turbines designed with a vertical axis. It has a good starting capacity and an insensitivity to wind direction. It works relatively at low wind speed in an easy installation. Savonius wind turbine faces major drawbacks, including some of the low efficiency and high negative torque created by the returning blade. Many attempts have been undertaken to optimize the blade’s shape to increase the performance of these wind turbines. The vertical axis is still under development. The elliptical-blades with a cut angle equal 47.50° have recently shown enhanced performance. In this study, we investigate the effect of Elliptical-bladed multistage Savonius Rotors (rotor aspect ratio, stage aspect ratio) on the performance by means of numerical simulation. The results obtained by comparison of one, two, and three-stage rotors indicate that the maximum power coefficient increase with a number of the stages (for the rotors with similar RAR of 0.7). Moreover, for the rotors with similar SAR of 0.7, the two stages have the highest performance than others.